Cultivar Development - Mumm, Rita H. (Open textbook library., 2023)
This open textbook places emphasis on the design of a process pipeline for continuous development of new improved cultivars as a means to implement the cycle of crop improvement. Essential topics in New Line Development and New Line Evaluation are addressed, such as choice of parents, creation of progeny, and evaluation and selection of progeny. Students learn to design a process pipeline to produce improved cultivars that meet a specific product target which represents stakeholders’ needs.